Arqueología molecular; pH adobe Tallan con presencia microorganismos para conservación preventiva; Sitio arqueológico Tangarará 3. - González Espino, David (2024)
The analysis of Taltan adobes as elements that serve for construction at the pH level provides new knowledge for intervention at the level of preventive conservation. The objective of the research is to carry out, through molecular archeology, an analysis of the pH in the adobe carving, determining the presence of microorganisms, as well as the acidity or alkalinity of the construction material and serving as a reference for preventive architectural conservation in the intervention at the sites. archaeological sites of the northern coast of Peru. The work methodology was determined by a quantitative approach, basic type and non-experimental design since no variable was manipulated, and a sample of twenty (20) adobes was used. As a result, we have a pH of 7.21, which is determined as slightly alkaline or basic, being an indicator that allows us to interpret the absence of humidity, and the presence of fungi in the adobes is determined. At the level of conclusions, it is determined that the soil material used to make Taltan adobes prevents water humidity in the processes known as percolation or leaching, slowing down the deterioration of the construction material over time.